Classification of trace elements in tissues from organic and conventional French pig production. (July 2018) - Parinet, Julien; Royer, Eric; Saint-Hilaire, Mailie; Chafey, Claude; Noël, Laurent; Minvielle, Brice; Dervilly-Pinel, Gaud; Engel, Erwan; Guérin, Thierry
Abstract: This study assesses the impact of the farming system on the levels of copper, zinc, arsenic, cadmium, lead and mercury in pig tissues from three types of production (Organic (n = 28), Label Rouge (n = 12) and Conventional (n = 30)) randomly sampled in different slaughterhouses. All the concentrations were below regulatory limits. In muscles, Cu, Zn and As were measured at slightly higher levels in organic samples but no differences between organic and Label Rouge was observed. Livers from conventional and Label Rouge pig farms exhibited higher Zn and Cd contents than the organic ones, probably due to different practice in zinc or phytase supplementation of fattening diets. Principal component analysis indicated a correlation between Cu and As concentrations in liver and carcass weight, and between Zn and Cd liver levels and lean meat percentage. The linear discriminant analysis succeeded in predicting the farming process on the basis of the lean meat percentage and the liver Cd level. Highlights: Trace elements in tissues from organic and conventional French pig production Significant differences were observed for some elements between types of farming. PCA analysis indicated that Cu and As, and Zn and were well correlated. Linear discriminant analysis predict the farming process (Conventional vs Organic).